2018
DOI: 10.1007/978-3-319-99704-9_33
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities and Benefits of Intermediate Care Units in Healthcare Systems from a Logistics Perspective

Abstract: Intermediate care units have been established as a response to the emerging challenges of healthcare systems to maintain high quality and continuous care. While the term is well known in both literature and practice, it lacks a unified definition. There is no common consensus of how intermediate care units can be successfully implemented and properly utilized in healthcare systems. Large variations of services in intermediate care units can be found. This literature review has structured the existing research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Many of the earlier studies of the effects of community hospitals have been small scale [31,32] or studies with methodological shortcomings [33]. However, several of the case studies found that the introduction of community hospitals and other forms of intermediate care units resulted in a reduction of unnecessary hospital admissions among older adults [31] as well as reductions in prolonged hospital stays and reduction in delayed discharges from the hospitals [34]. A US-study of a post-acute intermediate-care geriatric unit [35] indicate that such units also may represent a potential alternative to acute hospitalization for selected older patients.…”
Section: The Maws -Means To Achieve Care Integrationmentioning
confidence: 99%
“…Many of the earlier studies of the effects of community hospitals have been small scale [31,32] or studies with methodological shortcomings [33]. However, several of the case studies found that the introduction of community hospitals and other forms of intermediate care units resulted in a reduction of unnecessary hospital admissions among older adults [31] as well as reductions in prolonged hospital stays and reduction in delayed discharges from the hospitals [34]. A US-study of a post-acute intermediate-care geriatric unit [35] indicate that such units also may represent a potential alternative to acute hospitalization for selected older patients.…”
Section: The Maws -Means To Achieve Care Integrationmentioning
confidence: 99%
“…Interest in IMCUs has increased in both Europe and the United States. A systematic review has highlighted the positive effects of IMCUs on health systems, including reduced waiting times, improved synchronization of different medical resources, and flexible patient flow [12]. However, it also highlights the challenge of identifying this area of expertise as there is no shared understanding of this type of unit [12].…”
Section: Introductionmentioning
confidence: 99%